Effect of Ambient Wind Speed on Pressure Distribution and Smoke Movement in Single and Multiple Compartment Fires. Issue 8 (3rd August 2019) - Zhou, Yang; Bu, Rongwei; Gong, Junhui; Geng, Zhongyang; Fu, Huiai; Yi, Liang
ABSTRACT: In scenarios of compartment fire, natural smoke exhaust often confronts the challenge of environmental wind. In this work, a series of numerical simulations were conducted to study the influences of ambient wind speed, location of ventilation and fire source on pressure distribution and smoke movement in both single and multiple compartment fires. The results show that the pressure differential increases parabolically with the increasing ambient wind speed under the windward-leeward condition. The pressure differential and CO2 exhaust rate are positively correlated with the smoke outlet area, which shows an opposite trend with the air inlet area. Under the windward-leeward and windward-sideward conditions, the outlet flow velocity gets larger as the wind speed increases, but the wind pressure has minimal impact on smoke movement under leeward-sideward condition. The airflow velocity in windward-ceiling condition is higher than that in leeward-ceiling condition and both of them increase with the increasing wind speed. As the wind speed increases, the smoke stratification in the corridor is weakened and the pressure fluctuation is exacerbated in the multi-room fire, which is beneficial for smoke control. The results obtained in this work would provide a reference for the optimal design and management of building smoke control system.